2014
DOI: 10.1371/journal.pone.0110688
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Hydrogen Sulfide in Novel Rat Models of Non-Erosive Esophagitis

Abstract: Non-erosive esophagitis is a chronic inflammatory condition of the esophagus and is a form of gastroesophageal reflux disease. There are limited treatment options for non-erosive esophagitis, and it often progresses to Barrett’s esophagus and esophageal carcinoma. Hydrogen sulfide has been demonstrated to be a critical mediator of gastric and intestinal mucosal protection and repair. However, roles for H2S in esophageal mucosal defence, inflammation and responses to injury have not been reported. We therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Xu et al (2015) reported that pre-treatment with NaHS ameliorates high glucoseinduced inflammation in H9c2 cardiac cells, evidenced by the inhibition of IL-1β, IL-6, and TNF-α expression. Furthermore, treatment with an H 2 S donor in a rat model of non-erosive esophagitis markedly alleviated the inflammatory response and regulated serum IL-17 concentration (Zayachkivska et al, 2014). Thus, we speculate that H 2 S may serve as an anti-inflammatory agent in DSS-induced inflammation in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 72%
“…Xu et al (2015) reported that pre-treatment with NaHS ameliorates high glucoseinduced inflammation in H9c2 cardiac cells, evidenced by the inhibition of IL-1β, IL-6, and TNF-α expression. Furthermore, treatment with an H 2 S donor in a rat model of non-erosive esophagitis markedly alleviated the inflammatory response and regulated serum IL-17 concentration (Zayachkivska et al, 2014). Thus, we speculate that H 2 S may serve as an anti-inflammatory agent in DSS-induced inflammation in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 72%
“…This was supported by studies where it was shown that H2S treatment attenuates adherence of leukocytes to the vascular endothelium and impairs extravasation of leukocytes; however Inhibition of endogenous H2S rescued the phenotype [107, 108]. Recent studies related to sub-dermal inflammation, H2S treatment provides a protective function by suppressing leukocyte infiltration and edema formation [109]. Moreover, several groups have shown that H2S suppress the expression of cell adhesion molecules on both the endothelium (e.g., intercellular adhesion molecule (ICAM)-1 and P-selectin) and on the leukocyte (lymphocyte function-associated antigen (LFA)-1) [110, 111].…”
Section: Inflammation and H2s Signalingmentioning
confidence: 94%
“…H2S also increases phagocytosis of bacteria by macrophages, and promotes a shift of phenotype of macrophages to the "M2", pro-resolution state [14]. H2S donors can also reduce inflammation by reducing the expression of a number of proinflammatory cytokines (e.g., tumour necrosis factor (TNF)-α, interleukin (IL)-1β, IL-8, interferon (IFN)-Y but sparing of expression of the pro-inflammatory cytokine, IL-10 [10,11,15]. Inhibition of pro-inflammatory cytokine expression most likely occurs by suppression of nuclear factor ĸB (NFĸB) activity by H2S [16].…”
Section: Anti-inflammatory and Pro-resolution Effects Of Hydrogen Sulmentioning
confidence: 99%
“…IL-10-deficient mice exhibit impaired H2S synthesis in the colon (and these mice can spontaneously develop colitis) [7,17]. Administration of H2S donors increases IL-10 expression [7,15], while administration of IL-10 to the IL-10-deficient mice restored normal colonic H2S synthesis [7].…”
Section: Anti-inflammatory and Pro-resolution Effects Of Hydrogen Sulmentioning
confidence: 99%